Joint dominance and tacit collusion: An analysis of the Irish Vodafone/O2 case and the implications for competition and regulatory policy - Patrick Massey; Moore McDowell (University College Dublin, UCD School of Economics, 2008)
The paper takes as its starting point the Irish telecom regulator ComReg's finding of joint dominance by two firms in the mobile phone market in Ireland. The paper argues that the regulator's decision was inconsistent with the facts in the case. However, it argues that the case raises wider questions about the whole concept of joint dominance as it has evolved under EU competition law which in our view is confused. We regard the approach of the ECJ in trying to use a single approach to joint dominance in merger analysis and in competition analysis as unjustified, misguided and at odds with economic analysis.
hdl:10197/1344
Keywords: 330